UNDERSTANDING COGNITIVE LOAD IN HUMAN-MACHINE INTERACTIONS AT MRT TICKET VENDING MACHINES: A NASA TLX EVALUATION - Sugiono, Sugiono; Lukodono, Rio Prasetyo; Sudjono, Harry (JEMIS (Journal of Engineering & Management in Industrial System), 2024)
The provision of Mass Rapid Transit (MRT) and its supporting facilities in Jakarta necessitates an analysis of their user-friendliness for passengers. These facilities include information on various locations such as toilets, mosques, MRT card counters, ticket vending machines (TVMs), and signage directing passengers to the MRT. TVMs are machines that enable passengers to purchase MRT tickets and top up their card balances. A crucial aspect of evaluating TVM performance is assessing their user-friendliness, which is determined by the ease with which passengers can understand and operate them. This study aims to analyze the user-friendliness of TVMs at MRT stations using the NASA TLX approach. NASA TLX evaluates the impact of using TVMs based on mental, physical, and temporal demands, as well as performance, effort, and frustration. Data were collected through accidental sampling of respondents aged 18–28 years. The NASA TLX questionnaire explored users' cognitive perceptions of the TVMs' displays and procedures. The results will reveal how the factors measured by NASA TLX influence the interaction between passengers and TVMs at MRT stations. The findings will provide recommendations for MRT managers to enhance TVM designs and modify display procedures to improve user satisfaction.